The development and evaluation of chitosan-coated enzyme magnetic nanoparticles for cellulose hydrolysis - Park, Heejoon; Johnson, Patrick A. (Frontiers in Chemical Engineering, 2024)
The recycling capability, colloidal and thermal stability of exo-cellulase, endo-cellulase, and β-glucosidases with magnetic particles (MNPs) were evaluated. Co-precipitation and oxidation of Fe(OH)2 methods were used to fabricate magnetic nanoparticles. Three different enzymes were covalently bound to the surface of MNPs using 3-(aminopropyl) triethoxysilane (APTES) and a common protein crosslinking agent, glutaraldehyde. To evaluate the increase in colloidal dispersion stability, chitosan-coating was applied on MNPs and evaluated through particle settlement tests. The results showed that the chitosan-coated MNPs had 3.7 times higher colloidal dispersion stability than the bare MNPs. X-ray photoelectron spectroscopy (XPS) confirmed each magnetic nanoparticle surface modification step and successful enzyme binding. The optimum bioconjugate ratio in exo-cellulase, endo-cellulase, and β-glucosidases was evaluated, and having a high endo-cellulase bioconjugate in the reaction produced the highest glucose. The bioconjugates showed superior glucose productivity 39.4% at 65 o C and 22.2% at 88 o C in which the native enzyme is inactivated completely after 5 hours of exposure. Recycling stability studies showed approximately 78% of activity was retained after 10 cycles and 32% of activity was retained after 20 cycles. The bioconjugates demonstrated equivalent total product conversions as a single reaction of an equivalent amount of the native